How common are taste and smell abnormalities in COVID-19? A systematic review and meta-analysis - Shahzaib Ahmad; Anum Sohail; Muhammad Abubakar Shahid Chishti; Muhammad Aemaz Ur Rehman, MBBS; Hareem Farooq, MBBS (Journal of Taibah University Medical Sciences, 2022)
الملخص: أهداف البحث: يعد خلل الشم والذوق من الأعراض السريرية المبكرة الهامة لمرض كوفيد-19. تهدف الدراسة إلى حساب الانتشار التجميعي لهذه الأعراض؛ ثم مناقشة الآثار المحتملة على الممارسة السريرية مثل استخدامها كأدوات فحص ومؤشرات تشخيص محتملة. طرق البحث: باستخدام مجموعة من الكلمات المفتاحية ومصطلحات الميدلاين المعيارية، بحثنا عن الدراسات بالملاحظة في قواعد البيانات الخمس التالية: ''ميدلاين'' و ''سكوبس'' و''مكتبة كوكرين'' و ''شبكة العلوم'' و '' قوقل العلمي''. قام اثنان من الباحثين بفحص واختيار الدراسات، كما تم تقييم احتمالات التحيز في الدراسات المضمنة باستخدام مقياس نيوكاسل-أوتاوا. تم اتباع إرشادات ''بريزما'' لفحص المقالات النهائية وتحديدها وفقا لمعايير التضمين. كانت النتيجة المبلغ عنها للتحليل التجميعي هي معدل انتشار ضعف الشم والذوق المحسوب باستخدام نموذج التأثير العشوائي. النتائج: تم تضمين 17 دراسة مع حجم عينة إجمالي 4149 في هذا التحليل التلوي. من بين هؤلاء، أبلغ 2106 و 2676 مريضا عن درجة من الخلل الوظيفي الشمي و/أو الذوقي مع كوفيد-19؛ على التوالي. كانت النتائج المبلغ عنها من حيث الانتشار التجميعي، مع ضعف الذوق 57.33٪ والخلل الشمي 59.69٪، والذي يعتبر انتشارا كبيرا. الاستنتاجات: هناك معدل مرتفع لحدوث ضعف في حاسة الشم والذوق في مرض كوفيد-19. نظرًا لعدم وجود اختبار موضوعي للكشف عن ضعف الشم والذوق في معظم الدراسات، فمن المرجح أن يكون معدل الانتشار المرتفع الذي اكتشفناه أقل من الانتشار الحقيقي. هذا يعني أنه يجب على الأطباء استخدامها كمؤشرات مبكرة موثوقة لمرض كوفيد-19 وتوظيفها قبل فحص المرضى باختبارات باهظة الثمن. Abstract: Objective: Olfactory and gustatory dysfunction (OGD) are important early clinical symptoms of COVID-19. We aim to calculate the pooled prevalence of these symptoms and discuss the likely implications on clinical practice such as their use as screening tools and potential prognosis indicators. Methods: Using a combination of keywords and medical subject headings, we searched for observational studies in the following five databases: Medline/PubMed, Scopus, Cochrane Library, Web of Science, and Google Scholar. Two authors independently screened and selected the final articles according to the inclusion criteria. Two investigators independently assessed the risk of bias in individual studies using the Newcastle–Ottawa Scale. Heterogeneity and publication bias were also assessed. The reported outcome of the pooled analysis was the prevalence of OGD calculated using a random-effect model. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed to report results. Results: Seventeen studies with a total sample size of 4149 were included in this meta-analysis. Out of these, 2106 and 2676 patients reported some degree of olfactory and/or gustatory dysfunction with COVID-19, respectively. The reported outcomes were in terms of pooled prevalence, with gustatory dysfunction being 57.33% and olfactory dysfunction being 59.69%, a significantly high occurrence. Conclusion: There is a high occurrence of smell and taste impairment in COVID-19. Given the lack of objective testing for detecting OGD in most studies, the high prevalence found is likely to be an underestimation of the true prevalence. This implies that physicians must use them as reliable early indicators of COVID-19 and employ them before using expensive tests.